Geochemical data from core SEAL-20230070 ... - Martins, Alisson Klayton; Kochhann, Karlos Guilherme Diemer; Chiessi, Cristiano Mazur; Bauersachs, Thorsten; Zardin, Tamires N; de Carvalho Campos, Marília; Krahl, Guilherme; de Souza, Laís V; Crivellari, Stefano; Bahr, André; Kuhnert, Henning; Schwark, Lorenz; et al. (PANGAEA, 2024)
The dataset was obtained from the SEAL-20230070 core, located near the mouth of the São Francisco River in northeastern Brazil. The obtained proxies described the hydrological conditions in the river drainage area over the last ~20,000 years as a measure of fluctuations in monsoon intensity and changes in the intertropical convergence zone in the South Atlantic. Elemental ratios derived from sedimentary XRF reflect high influxes of terrigenous sediments during the Heinrich Stadial (H1) and Younger Dryas (YD) events; paleoproductivity proxies show that the abundance of more oligotrophic planktonic foraminifera changed during the H1 and YD events. TEX86 data and the BIT index, respectively, indicate changes in sea surface temperature and the input of organic matter from the continent to the ocean. The age model was constructed using five radiocarbon dates measured on planktonic foraminifera. ...